New And Improved Versions Of Genetic And PSO Algorithms For A Class Of Hybrid Systems And Steel Annealing Process - Arumugam, M. Senthil (2008)
This thesis investigates the optimal control of a class of single stage and two-stage hybrid manufacturing systems with a real time application of Steel Annealing Processes(SAP) via various versions of real coded genetic and particle swarm optimization (PSO) algorithms.